A history of mathematics - Merzbach, Uta C.; Boyer, Carl B. (John Wiley & Sons, Ltd., 2011)
This book teaches about the history of humankind's relationship with numbers, shapes, and patterns. This revised edition features up-to-date coverage of topics such as Fermat's Last Theorem and the Poincare conjecture, in addition to recent advances in areas such as finite group theory and computer-aided proofs. Includes information about the age of Plato and Aristotle, Poincare and Hilbert, the Pythagorean theorem, the golden mean. It explores the history of mathematics and the men and women who created it.